Efficacy of laser interstitial thermal therapy (LITT) for newly diagnosed and recurrent IDH wild-type glioblastoma. Issue 1 (6th April 2022) - de Groot, John F; Kim, Albert H; Prabhu, Sujit; Rao, Ganesh; Laxton, Adrian W; Fecci, Peter E; O'Brien, Barbara J; Sloan, Andrew; Chiang, Veronica; Tatter, Stephen B; Mohammadi, Alireza M; Placantonakis, Dimitris G; et al.
Abstract: Background: Treatment options for unresectable new and recurrent glioblastoma remain limited. Laser ablation has demonstrated safety as a surgical approach to treating primary brain tumors. The LAANTERN prospective multicenter registry (NCT02392078) data were analyzed to determine clinical outcomes for patients with new and recurrent IDH wild-type glioblastoma. Methods: Demographics, intraprocedural data, adverse events, KPS, health economics, and survival data were prospectively collected and then analyzed on IDH wild-type newly diagnosed and recurrent glioblastoma patients who were treated with laser ablation at 14 US centers between January 2016 and May 2019. Data were monitored for accuracy. Statistical analysis included individual variable summaries, multivariable differences in survival, and median survival numbers. Results: A total of 29 new and 60 recurrent IDH wild-type WHO grade 4 glioblastoma patients were treated. Positive MGMT promoter methylation status was present in 5/29 of new and 23/60 of recurrent patients. Median physician-estimated extent of ablation was 91%-99%. Median overall survival (OS) was 9.73 months (95% confidence interval: 5.16, 15.91) for newly diagnosed patients and median post-procedure survival was 8.97 months (6.94, 12.36) for recurrent patients. Median OS for newly diagnosed patients receiving post-LITT chemo/radiation was 16.14 months (6.11, not reached). Factors associated with improved survival were MGMT promoter methylation, adjuvant chemotherapy within 12 weeks, and tumor volume <3 cc. Conclusions: Laser ablation is a viable option for patients with new and recurrent glioblastoma. Median OS for IDH wild-type newly diagnosed glioblastoma is comparable to outcomes observed in other tumor resection studies when those patients undergo radiation and chemotherapy following LITT.